TMD‐Based Phototransistors: Anomalous Broadband Spectrum Photodetection in 2D Rhenium Disulfide Transistor (Advanced Optical Materials 23/2019). Issue 23 (3rd December 2019) - Xiang, Du; Liu, Tao; Wang, Junyong; Wang, Peng; Wang, Lin; Zheng, Yue; Wang, Yanan; Gao, Jing; Ang, Kah‐Wee; Eda, Goki; Hu, Weida; Liu, Lei; et al.
Abstract : In article number 1901115, Du Xiang and co‐workers report the photodetection in 2D multilayer ReS2 transistor via bolometric mode, which relies on light heating induced conductance change, making it feasible for sub‐bandgap photon detection. The findings would extend the response spectrum of large‐bandgap transition metal dichalcogenides for broadband photodetectors.